Ribosomal movement impeded at a pseudoknot required for frameshifting. - Tu, C (1992)
Translational frameshifting sometimes occurs when ribosomes encounter a "shift" site preceding a region of unusual secondary structure, which in at least three cases is known to be a pseudoknot. We provide evidence that ribosomes have a decreased rate of movement through a pseudoknot required for frameshifting. These paused ribosomes are directly situated over the shift sequence. Ribosomal pausing appears to be necessary but not sufficient for frameshifting.